Yemeni EFL University Students’ Attitudes towards Using Eliademy as a Learning Tool - Al-Mekhlafi, Mohammad Abdu Ahmad; Al-Showthabi, Abdulrahim Ali; Alshargabi, Eman Abdulghani (Journal of Educational and Psychological Sciences, 2021)
The purpose of this quantitative study was to investigate the attitudes of Yemeni EFL students towards using Eliademy as a learning tool. The second goal was to explore any similarities and differences between graduate and undergraduate students and between males and females in terms of their attitudes towards using Eliademy as a learning tool. This study employed a quantitative approach. One hundred and twenty students of the fourth level of the B.Ed. program and forty students enrolled in the M.Ed. program at the Department of English in the College of Education at Sana’a University in Yemen participated in this study during the academic year 2017 /2018. Data were collected using a questionnaire whose analysis revealed a positive attitude towards using Eliademy as a learning tool. The findings of this study indicated that the highest mean average among the five components of the attitude scale was the Behavioral Engagement (BE) (M= 4.09), followed by Developing Language Skills (M= 4.04) and the Linguistics Confidence (M= 3.92). Finally came the Attitude to Learning Linguistics with Technology (M= 3.76) and the Technology Confidence (M= 3.56). This study concluded that there was a statistically significant difference between the mean of the undergraduate and graduate students towards using Eliademy as a learning tool in favor of the graduate students. Furthermore, there was no statistically significant difference between male and female students in terms of their attitudes towards using Eliademy. This study ends with some pedagogical implications and directions for future research studies.
Keywords: Students’ attitudes; Eliademy; Gender; Yemen